Pelatihan Pekerjaan Plafon Gybsum untuk Kelompok Tukang Lokal di Oetalu, Kabupaten Kupang: Gypsum Ceiling Work Training for Local Craftsmen in Oetalu, Kupang Regency - Usboko, Gregorius Paus; Pedo, Krisantus Satrio Wibowo; Bees, Azarya; Bela, Krisantos Ria (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
One type of ceiling often found in commercial buildings today is gypsum board. Slowly, the ceiling of the house made directly from wooden ribs and plywood began to decrease, and in general, local artisans in the Oetalu area, East Penfui, Kupang Regency, are not yet skilled in installing gypsum ceilings and do not even know how to do it. What often happens is that foreign artisans from Java or Sulawesi do gypsum ceiling work. This is a problems for empowering and developing local artisans' skills. In addition to the problems mentioned above, to become a professional artisan in construction, you must be certified by a certification body and the public works department. The qualifications of gypsum ceiling artisans are at class/level 3, and their classification is gypsum ceiling artisans with the number TA013. Ownership of a craftsman's competency certification is an obligation for construction workers as regulated in the Construction Services Law. After that, a training activity was carried out with lectures and practical training for three days, starting from purchasing materials, assembling steel frames, and installing gypsum boards, and ending with finishing. The results of this training activity are that the training participants, in this case, members of the local artisans group, are skilled in gypsum ceiling work and are ready to become gypsum ceiling workers, ready to take the craftsman certification test organized by the association or public works department. There was a significant increase in knowledge and skills among local artisans in gypsum ceiling installation work.